Educational Financing Management Through Entrepreneurship Development At Jabal Nur Kandis Islamic Boarding School - Ningrum, Agnes Ika; Irawati, Irawati; Setyaningsih, Rini (Journal of Sustainable Education, 2024)
This research aimed at 1) Knowing the implementation of educational funding management through entrepreneurship development, 2) Know the contribution results of entrepreneurship development at Islamic Boarding School of Jabal Nur Kandis, Riau.  This research used qualitative method. The main informant of this research was school treasurer, and additional informants were the head of Islamic boarding school and person in charge of business unit.  The object of this research was Islamic Boarding School of Jabal Nur Kandis, Riau.  The findings of this research showed that one of the 1) Planning in funding at Islamic boarding schools was creating business units to assist Islamic boarding school operations. The implementation of education funding at Islamic boarding schools was in accordance with the needs every unit based on the principle of education finance.  The implementation of education funding in the form of recording incoming money from tuition fees, annual fees and from Islamic boarding school business units and outgoing money based on the budget for activities that have been planned.  Educational Supervision was conducted directly by the leadership and treasurer of the Islamic boarding school. 2) The results and contributions in developing entrepreneurship were focused on existing business units and a portion of the sales profit that would be allocated to assist Islamic boarding school operations.